Bioinspired Models of Network, Information, and Computing Systems 4th International Conference, BIONETICS 2009, Avignon, France, December 9-11, 2009, Revised Selected Papers - Altman, Eitan.; Carrera, Iacopo.; El-Azouzi, Rachid.; Hart, Emma.; Hayel, Yezekael. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Conference on Bio-Inspired Models of Network, Information, and Computing Systems (Bionetics). The event took place in the city of Avignon in December 2009. Bionetics main objective is to bring bio-inspired paradigms into computer engineereing and networking, and to enhance the fruitful interactions between these fields and biology. The program of the conference includes applications of various paradigms that have their origin in biology: population dynamics, branching processes, ant colony optimization. The 19 revised full papers were carefully reviewed and selected and cover a broad range of important issues in areas related to bio-inspired technologies.